Independent Tuning of Nano‐Ligand Frequency and Sequences Regulates the Adhesion and Differentiation of Stem Cells. Issue 40 (20th August 2020) - Min, Sunhong; Jeon, Yoo Sang; Jung, Hee Joon; Khatua, Chandra; Li, Na; Bae, Gunhyu; Choi, Hyojun; Hong, Hyunsik; Shin, Jeong Eun; Ko, Min Jun; Ko, Han Seok; Jun, Indong; et al.
Abstract: The native extracellular matrix (ECM) can exhibit heterogeneous nano‐sequences periodically displaying ligands to regulate complex cell–material interactions in vivo. Herein, an ECM‐emulating heterogeneous barcoding system, including ligand‐bearing Au and ligand‐free Fe nano‐segments, is developed to independently present tunable frequency and sequences in nano‐segments of cell‐adhesive RGD ligand. Specifically, similar exposed surface areas of total Fe and Au nano‐segments are designed. Fe segments are used for substrate coupling of nanobarcodes and as ligand‐free nano‐segments and Au segments for ligand coating while maintaining both nanoscale (local) and macroscale (total) ligand density constant in all groups. Low nano‐ligand frequency in the same sequences and terminally sequenced nano‐ligands at the same frequency independently facilitate focal adhesion and mechanosensing of stem cells, which are collectively effective both in vitro and in vivo, thereby inducing stem cell differentiation. The Fe/RGD‐Au nanobarcode implants exhibit high stability and no local and systemic toxicity in various tissues and organs in vivo. This work sheds novel insight into designing biomaterials with heterogeneous nano‐ligand sequences at terminal sides and/or low frequency to facilitate cellular adhesion. Tuning the electrodeposition conditions can allow synthesis of unlimited combinations of ligand nano‐sequences and frequencies, magnetic elements, and bioactive ligands to remotely regulate numerous host cells in vivo. Abstract : A heterogeneous barcoding system including RGD‐bearing Au and RGD‐free Fe nano‐segments is developed to independently present tunable nano‐ligand frequency and sequences without modulating nanoscale and macroscale ligand density. The low‐frequency and terminally sequenced nano‐ligands are demonstrated as novel and independent parameters facilitating focal‐adhesion‐mediated mechanotransduction of stem cells, both in vitro and in vivo, which facilitate their subsequent differentiation.